Facilitators and barriers to education for chiropractic students with visual impairment - Joshi, Aditi (J Chiropr Educ, 2019)
OBJECTIVE: The purpose of this study was to document the academic experiences of students with visual impairment in a doctor of chiropractic program. METHODS: Ten participants were recruited, including 3 students who are “legally blind,” 2 student notetakers, 3 faculty members who taught students with visual impairment, and 2 staff members from the Disability Services Office. For this qualitative study, the students were recruited through the Disability Services Office. The participants were audiotaped during approximately 1-hour interviews conducted in a semistructured manner within a private setting (a quiet office) on the campus during office hours. Thematic analysis was conducted using a deductive method for codes and an inductive method for themes. RESULTS: We identified facilitators and barriers to the education of students with visual impairment. Notable facilitators were planning for accessible educational materials, accessibility of workable space, and support systems, such as notetakers and close interaction with faculty. Notable barriers were attitudes of students with visual impairment toward their education, lack of personnel training, and lack of disability awareness in the campus community. CONCLUSION: Meticulous planning of resources and communication are key to enriching academic experiences of students with visual impairment.